The Case For Corporate Responsibility: Arguments From The Literature - Lucy da Piedade; Adele Thomas (SA Journal of Human Resource Management, 2006)
Heightened scrutiny of organisations and ever increasing stakeholder demands for organisations to respond to issues within broader society, make it imperative that organisational leaders understand why they should undertake corporate responsibility initiatives. This literature review (part one of a two part study) investigates the issues that should be addressed by organisations under the banner of corporate responsibility, including the definition of corporate responsibility, its extent and boundaries and the business case for corporate responsibility. This background provides a basis for an exploratory study (part two) of how South African organisations should frame the case for corporate responsibility and how investment in this area can be assessed.